Nutrición en el paciente diabético y la intervención en su calidad de vida en los integrantes del Club de Diabéticos del Hospital Regional Isidro Ayora de la ciudad de Loja - Yaguachi Tandazo, María del Carmen (2015)
Mellitus Diabetes is a group of metabolic diseases characterized by hyperglycemia, which may be associated with the consumption of unhealthy diet, physical inactivity, obesity, excessive soft drinks, alcohol, refined products, and some genetic factors. This research study was aimed to know how diabetic patients’ nutrition intervenes in their quality of life, furthermore to evaluate patients’ nutritional status by using anthropometric measurements, to relate the values of glycosylated hemoglobin to diabetic patient’s eating habits and determine if the patient’s socioeconomic status affects their nutritional level. This research is framed into a quantitative, qualitative, cross-sectional and descriptive study. The sample are 56 patients diagnosed with Type 2 - Mellitus Diabetes from the Amigos Dulces Diabetic Club; I applied a survey to determine the consumption of energy and non-energy nutrients, I also measured and weighed for each patient to determine the body mass index (BMI), SF36 health questionnaire and it was also performed a glycosylated hemoglobin test. The results showed that most of the studied population has a high protein intake (48%) a week, followed by daily consumption of carbohydrates (36%) and fat (45%). In addition, 91% of studied patients do not have good control of glycosylated hemoglobin which is very important in a diabetic patient, and this situation goes in relation to their quality of life determined through SF36 health questionnaire. Keywords: Mellitus Diabetes, nutritional status, quality of life.